Decentralization in Action: Decentralization Implementation in Jogyakarta City - ACHMAD NURMANDI (Laboratory ofcoyemmental Studies UMY, 2010)
The aim of paper is to explore implementation of decentralization in Jogyakarta City after decentralization policy launched in 2001 by Megawati Administration. The research method is comparative study by using secondary data and primary data from comparison result of city condition before (pre-2002) and after the implementation of regional autonomy (2002-2008) was implemented. The study found that municipal government had good performance of economic aspect, social aspect and bureaucracy of city. However, environmental aspects of city autonomy showed quite poor performance. In implementing the decentralization policy, the good capability and vision of mayor had, the staff group of an organization, the complexity of the tasks, and the organizational communication were the factors that get must careful attention due to they influence most its success. Theoretically, the implementation of asymmetric pattern of autonomy contribute to development of the decentralization theory in the future